A teacher for all generations: essays in honor of James C. Vanderkam - Mason, Eric Farrel; VanderKam, James C. (Journal for the study of Judaism, 2025)
Pt. 1. The Hebrew Bible and the ancient Near East -- pt. 2. Qumran and the Dead Sea scrolls -- pt. 3. Early Judaism -- pt. 4. Studies on Enoch and Jubilees -- pt. 5. The New Testament and early Christianity